THE RECLAMATION TECHNICAL PLAN ON ANDESIT MINING IN DADIREJO VILLAGE, BAGELEN DISTRICT, PURWOREJO REGENCY, CENTRAL JAVA PROVINCE - Boy Arif Raja ihutan Siregar , Dian Hudawan Santoso , Muammar Gomareuzzaman (Techno LPPM, 2022)
This research was conducted on an andesite mining area in Dadirejo Village, Bagelen District, Purworejo Regency, Central Java Province. The mine has stopped operating since 2018 until the end of 2019. Since the mining activity stopped, there have been no signs of management being carried out so that environmental degradation has occurred in the geophysical aspect at the research site. From the problems mentioned earlier, this study aims to determine the level of environmental damage in order to determine the technical planning of reclamation. The research methods used are survey and mapping to measure the level of environmental damage, laboratory analysis to determine soil fertility, appraisal to evaluate environmental damage, and data analysis to determine reclamation directions. The results of the evaluation of the level of environmental damage, the research location is classified as class III, namely the heavily damaged category with a value of 16. The reclamation direction is the manufacture of a bench terrace with a height of 2 m and a width of 4 m with a slope of 45o, a drainage channel with a height, and a holding pond. The re-vegetation technique was carried out in monoculture at a level with a spacing of cassava 0.7 mx 0.6 m, peanuts 0.4 mx 0.15 m, maize 0.2 mx 0.7 m, while the bottom of the mine was intercropped with a distance of 0.7 m. planting 1 mx 1 m.